Population of Herbivorous and Carnivorous Arthropods in Rice Field Ecosystem Modified with Vermicompost and Flower Plants - Suparni Suparni; Nugroho Susetya Putra; Suputa Suputa (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Biological diversity index could be used as an option to assess the stability of an agricultural ecosystem. This limited field research was aimed to determine the effect of vermicompost and flowering plants (Asteraceae) to the diversity of herbivore and carnivore arthropods (M+). Conventional treatment with the application of non-organic fertiliser and without the addition of flowering plant was used as control (M0). Sampling was conducted using insect nets, and began at 30 days after planting (DAT), and repeated every other week until before harvesting. The results showed that the diversity of herbivore and carnivore arthropods in modified plots with organic fertiliser worm cast and flower plants/habitat manipulated system (M+) was moderate (herbivores: Shannon diversity index from 1.1 - 2.2; carnivores: 1.93 - 2.09), as well as the diversity of arthropods in the field of non-modified/custom system (M0) (herbivores: Shanon index of 1.2 - 1.7; carnivore: 1.34 - 2.18). Meanwhile, the number of arthropod species found in the M+ plot was 59 species, consisted of 22 herbivores and 37 carnivores (9 order, 32 families, and 35 genera). Number of arthropods found in the M0 plot was 54 species, consisted of 17 species of herbivores and 37 species of carnivores (7 orders, 28 families, and 30 generas). Statistical analysis showed that there was no significant difference in the plot diversity M+ and M0. Nevertheless, mean diversity of the M+ plot tended to be higher (Shannon Index herbivore and carnivore = 1.6 = 2.01) compared with M0 plot (herbivore and carnivore = 1.45 = 1.76).